Power Flow Analysis of the Main Reducing Gear of Coaxial Counter-rotating High-speed Helicopter - Zhang Shifei; Chen Peng; Wu Wenmin; Xia Fuchun; Liu Lei (Jixie chuandong)
A mechanism scheme of main reducing gear of coaxial counter-rotating high-speed helicopter is studied,and a rapid evaluation on the gear power flow for designers is provided. Firstly,the unite analysis method of gear is introduced into the analysis of the helicopter main reducing gear,and the mathematical model of gear is built. Then,all types of power flow of the helicopter main reducing gear are summarized. Finally,the power flow type of the helicopter main reducing gear and the flying state（ forward flight state,alter course state,etc） effect on the efficiency are studied.